2023
DOI: 10.3389/fimmu.2023.1095943
|View full text |Cite
|
Sign up to set email alerts
|

gC1qR: A New Target for Cancer Immunotherapy

Abstract: Although breakthroughs in cancer treatment have been achieved, immunotherapy yields only modest benefits in most patients. There is still a gap in clarifying the immune evasiveness and immune-resistance mechanisms. Identifying other candidate targets for cancer immunotherapy is therefore a clear unmet clinical need. The complement system, a pillar of innate immunity, has recently entered the limelight due to its immunoregulatory functions in the tumor microenvironment (TME). In particular, gC1qR, a receptor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
(119 reference statements)
1
3
0
Order By: Relevance
“…The novel interaction between gC1qR and HYAL2 unveiled another regulatory role of gC1qR: by acting on HA metabolism, gC1qR may control the key functions of HA in tumor progression and its involvement in most of the hallmarks of cancer, such as sustenance of proliferative signaling and tumorpromoting inflammation, evasion of apoptosis, induction of angiogenesis, promotion of invasion and metastases, deregulation of energy metabolism and evasion of the immune response (4). Our findings lend credence to recent literature which describe gC1qR as an immunoregulator of TME, determining progression and metastatic properties of cancer c e l l s , t h u s , b e c o m i n g a n o v e l p r o m i s i n g t a r g e t fo r immunotherapy (51). Peerschke et al already demonstrated that the blockage of gC1qR with the monoclonal antibody 60.11 caused a reduction in MPM tumor size due to apoptosis enhancement and decreased neovascularization (26).…”
Section: Discussionsupporting
confidence: 89%
“…The novel interaction between gC1qR and HYAL2 unveiled another regulatory role of gC1qR: by acting on HA metabolism, gC1qR may control the key functions of HA in tumor progression and its involvement in most of the hallmarks of cancer, such as sustenance of proliferative signaling and tumorpromoting inflammation, evasion of apoptosis, induction of angiogenesis, promotion of invasion and metastases, deregulation of energy metabolism and evasion of the immune response (4). Our findings lend credence to recent literature which describe gC1qR as an immunoregulator of TME, determining progression and metastatic properties of cancer c e l l s , t h u s , b e c o m i n g a n o v e l p r o m i s i n g t a r g e t fo r immunotherapy (51). Peerschke et al already demonstrated that the blockage of gC1qR with the monoclonal antibody 60.11 caused a reduction in MPM tumor size due to apoptosis enhancement and decreased neovascularization (26).…”
Section: Discussionsupporting
confidence: 89%
“…Protein methylation plays a crucial role in tumor development and is involved in diverse biological processes, especially regulating protein-protein interactions that contribute to abnormal signal transduction and disease development. [30,31] CyPA and CD147 are regarded as essential ligand and receptor that activate multiple oncogenic signaling pathways, and agents that interfere with the interaction between CD147 and CyPA have the potential to inhibit tumor progression. [25] In our study, the dimethylation of CD147 at Lys148 had a potential influence on protein conformation, which increased the binding capacity of CyPA to CD147, and in turn activated the p38-ZBTB32 signaling, leading to increasing NSCLC cell-derived CCL5 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that targeting gC1qR-expressing cells with C1q induces an antiproliferative response ( 38 ). Because high gC1qR expression by most cancer cells is associated with poor survival, gC1qR has become a potential prime target for the development of anti-cancer therapy ( 43 , 44 ). Indeed, we are very much aware that targeting such a ubiquitously expressed, multifunctional, and multicompartmental molecule, would theoretically present an undesirable collateral risk since it has the potential to lead to deleterious off-target blockade of important biological functions.…”
Section: Preliminary Proof-of-concept Studies In Animal Modelsmentioning
confidence: 99%